Binary spherical particle mixed beds: porosity and permeability relationship measurement - Mota, M. (2001)
A continuous function relating the porosity of a mixture, ε, and the large particle volume fraction, xD, of binary mixtures of spherical particles has been established. The incorporation of the proposed porosity model into the convencional Kozeny-Carman equation gives a good agreement between the measured and the predicted permeability vs. xD. Based on this relationship and on the dependence of ε vs. xD a model predicting tortuosity and permeability was obtained, having demonstrated that the tortuosity may significantly alter the permeability of a mixed bed. The proposed model shows that the simulated permeability curve presents a minimum for xD values that are specified by the particle size ratios. The proposed model may be useful for the analysis of transport phenomena in granular beds as well as in engineering applications.